Polypoid lesions of the gallbladder: report of 160 cases with special reference to diagnosis and treatment in China - Guo, Jingjing (Int J Clin Exp Pathol, 2015)
Background: The preoperative diagnosis of gallbladder polypoid lesions is difficult, justifying the lack of consensus on the appropriate treatment. Objective: The aim of this study was to identify the characteristics of each type of polypoid lesion of the gallbladder and the indications for surgery. Methods: Between January 1999 and December 2012, clinical data were retrospectively correlated with the histopathologic characteristics of polypoid lesions in 160 patients who underwent cholecystectomy. Results: A total of 160 patients with benign polypoid lesions (including 49 tumor-like lesions and 75 adenomas) and 14 patients with malignant polypoid lesions (including 2 adenocarcinomas and 12 adenomas with malignant changes) were included in this study. One hundred and five (65.6%) of the patients had associated symptoms, and 70 (43.8%) had gallstones. Of the 49 patients with tumor-like lesions, 49 (100%) were correlated with chronic cholecystitis. A total of 72 (83.8%) patients with neoplasms had a single polyp compared with 25 (59.5%) of those with non-neoplastic polyps. The mean age of the patients with malignancy was 59.07±13.465 years, and 12 (85.7%) of these patients were over 50 years of age. The mean diameters of the benign and malignant polyps were 1.0±0.77 cm and 2.15±1.16 cm, respectively. Ten (100%) of the patients with malignancy had polyps of over 1 cm in size, as shown by ultrasound. Conclusion: Our findings indicate that tumor-like lesions, adenomas, and adenocarcinomas are the most common polypoid lesions of the gallbladder. Cholecystecomy should be done in patients with symptoms. The risk of malignancy is high in patients over 50 years of age; those with polyps with diameters of greater than 10 mm; and those with single polypoid lesions. The remainder of PLG patients without cholecystectomy should be followed up at regular intervals.